Healthcare Disparities - Eileen Van Schaik; Alex Howson; Janice Sabin (Association of American Medical Colleges, 2014)
Abstract This course on healthcare disparities is designed to increase awareness about racial and ethnic disparities across the spectrum of healthcare services and examine the use of patient-centered communication skills to minimize these disparities. This course includes peer-reviewed research, interactive case studies, and multimedia assessments that address topics including how the patient-physician relationship can contribute to disparities and how unconscious bias may conflict with consciously-held egalitarian values. The full course was evaluated using a randomized-controlled trial with a national sample of 130 physicians and resident physicians. It appears to have global effects on physicians' knowledge of disparities, attitudes toward unconscious bias, and satisfaction with virtual patient encounters.